Skrining fitokimia dan isolasi senyawa flavonoid dari ekstrak etanol biji buah menteng (Baccaurea racemosa (Reinw.) Müll.Arg). - Sarmadansyah Sarmadansyah; Haris Munandar Nasution; Anny Sartika Daulay; Daeng Elysa Putri Mambang (Journal of Pharmaceutical and Sciences, 2023)
Menteng or kepundung is a fruit-producing tree. At first glance, Menteng or kepundung fruit resembles duku fruit with a variety of tastes (sour) and sweet. Menteng originates from Malaysia, Sumatra, Java and Bali. The purpose of this study was to determine the class of chemical compounds found in Menteng fruit seeds and to determine the characteristics of the fruit seed extract isolates by UV spectrophotometry and IR spectrophotometry. This research includes several processes, namely manufacturing simplicia from menteng fruit seeds, phytochemical screening, and simplicia characterisation. The process of making extracts from menteng fruit seed Simplicia, after that extract analysis using paper chromatography (KKt) method, then separation (isolation) of the extract with preparative paper chromatography (KKt) method, tested the purity of isolates by two-way paper chromatography (KKt), and characterisation of isolate crystals by UV spectrophotometry and IR spectrophotometry. The results of the simplicial characterisation of Menteng fruit seeds (Baccaurea racemose (Reinw.) Müll. Arg) are 4% water content, 36.81% seawater content, 8.79% ethanol soluble extract, 1.26% ash content, 1.26% ash content. Insoluble 0.5% acid. Phytochemical screening showed positive alkaloids, flavonoids, steroids/triterpenoids and glycosides, while tannins and saponins were negative. From 400 grams of simplicia, 93.3 grams of condensed extract was produced. Characterisation of isolate crystals UV spectrophotometry showed a wavelength of 280 nm, which is suspected to be a flavonoid. The results of the IR spectrophotometry showed aliphatic O-H, C-H, C=O, C-H, C-O and C=C groups.